Pelatihan Pembelajaran Blended Learning Melalui Metode Flipped Classroom Bagi Guru SD Negeri Ciheuleut 1 Kota Bogor - Kristyowati, Dyah (MALLOMO: Journal of Community Service, 2024)
This community service program aims to increase the knowledge and understanding of elementary school teachers about blended learning strategies, improve their ability to combine technology and flipped classroom models in learning, and also train teachers on how to implement blended learning using the flipped classroom method. The methodology used in this community service activity consists of four stages, namely the preparation stage, the implementation stage, the evaluation stage, and the post-evaluation stage. The implementation of this community service activity aims to increase the capacity of teachers to implement blended learning through the flipped classroom method. This community service activity program results in increasing the knowledge, understanding, and skills of elementary school teachers in compiling and designing blended learning using the flipped classroom method. The results were obtained after the implementation of training for elementary school teachers in SD Negeri Ciheuleut 1Bogor . The ability of teachers to compile blended learning can be trained and improved, and as many as 75% of teachers have been able to carry out blended learning through the flipped classroom method adapted to school conditions and the local environment, namely SD Negeri Ciheuleut 1 Bogor.